Outpatient versus inpatient superficial parotidectomy: clinical and pathological characteristics - Daniel J. Lee; David Forner; Christopher End; Christopher M. K. L. Yao; Shireen Samargandy; Eric Monteiro; Ian J. Witterick; Jeremy L. Freeman (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Superficial parotidectomy has a potential to be performed as an outpatient procedure. The objective of the study is to evaluate the safety and selection profile of outpatient superficial parotidectomy compared to inpatient parotidectomy. Methods A retrospective review of individuals who underwent superficial parotidectomy between 2006 and 2016 at a tertiary care center was conducted. Primary outcomes included surgical complications, including transient/permanent facial nerve palsy, wound infection, hematoma, seroma, and fistula formation, as well as medical complications in the postoperative period. Secondary outcome measures included unplanned emergency room visits and readmissions within 30 days of operation due to postoperative complications. Results There were 238 patients included (124 in outpatient and 114 in inpatient group). There was no significant difference between the groups in terms of gender, co-morbidities, tumor pathology or tumor size. There was a trend towards longer distance to the hospital from home address (111 Km in inpatient vs. 27 in outpatient, mean difference 83 km [95% CI,- 1 to 162 km], p = 0.053). The overall complication rates were comparable between the groups (24.2% in outpatient group vs. 21.1% in inpatient, p = 0.56). There was no difference in the rate of return to the emergency department (3.5% vs 5.6%, p = 0.433) or readmission within 30 days (0.9% vs 0.8%, p = 0.952). Conclusion Superficial parotidectomy can be performed safely as an outpatient procedure without elevated risk of complications. Graphical abstract